Manufacturing method of polarizing membrane, and manufacturing method of polarizing film

By dyeing, cross-linking and stretching during transportation during polarized film manufacturing, and applying liquid under appropriate humidity for components to penetrate and dry, resource waste and environmental protection problems in the prior art are solved, and high polarization and good mechanical properties are achieved.

JP2025061732AInactive Publication Date: 2025-04-11NITTO DENKO CORP
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2025008193
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-09-20
Filing Date
2025-01-21
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, when manufacturing polarized films, adding ingredients to the treatment bath will lead to large quantities of products and need to process waste liquid, which can cause waste of resources and environmental protection problems.

Method used

During the polarized film manufacturing process, a polarized film with a water content of X% or more is dyed, cross-linked and stretched when transporting in the long direction, and a liquid is applied under appropriate humidity conditions so that the components are fully permeated and dried, forming a polarized film with high polarization.

Benefits of technology

The high polarization degree and good mechanical properties of the polarized film are achieved, while reducing resource waste and the need to process waste liquid, improving production efficiency and environmental protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061732000001
    Figure 2025061732000001
  • Figure 2025061732000002
    Figure 2025061732000002
  • Figure 2025061732000003
    Figure 2025061732000003
Patent Text Reader

Abstract

To provide a manufacturing method of a polarizing membrane, which enables any component to be contained easily and sufficiently in a polarizing membrane, the polarizing membrane having a satisfactory degree of polarization.SOLUTION: A manufacturing method of a polarizing membrane includes: a step (I-1) of manufacturing a polarizing membrane containing water by applying at least a dyeing step, a cross-linking step and an extension step to a polyvinyl alcohol-based film while conveying the polyvinyl alcohol-based film in a length direction; a step (I-2) of manufacturing a polarizing membrane in which a component in a liquid is impregnated by applying a step of applying the liquid to the obtained polarizing membrane containing water in a state where a moisture percentage of the polarizing membrane is X wt.% or more; and a step (I-3) of manufacturing a dried polarizing membrane by applying a drying step to the obtained polarizing membrane in which the component in the liquid is impregnated, where a condition of the formula (1) is satisfied: X (wt.%) / thickness (μm) of the dried polarizing membrane>1 (1) (in the formula, X is 10 to 70).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polarizing membrane and a method for producing a polarizing film. [Background technology]

[0002] Conventionally, polarizing films (polarizers) have been used in various image display devices such as liquid crystal display devices and organic EL display devices. ) has both high transmittance and high polarization, and is therefore popular as a dyed (iodine or Polyvinyl alcohol film (containing dichroic substances such as dichroic dyes) is used. The polarizing film is formed by treating a polyvinyl alcohol film in a bath (treatment bath), for example, as follows: The fiber is produced by subjecting the fiber to various treatments such as dyeing, crosslinking, stretching, etc., and then drying. The optical film is usually coated with a protective film such as triacetyl cellulose on one or both sides. It is used as a polarizing film (polarizing plate) laminated using

[0003] As a method for producing a polarizing film, for example, Patent Documents 1 and 2 disclose a method for producing a polarizing film using zinc, copper, aluminum, etc. By adding components such as metal salts containing It is disclosed that the durability of the membrane is improved. A method for producing a polarizing film has been disclosed in which a component such as a fluorine compound is added to the treatment bath. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2016 / 117659 [Patent Document 2] JP 2006-047978 A [Patent Document 3] JP 2008-46257 A [Patent Document 4] Japanese Patent Application Publication No. 6-172554 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the manufacturing method of a polarizing film, when the above-mentioned components are added to the processing bath, However, there are problems in that the amount of the treatment solution used becomes enormous and waste liquid treatment is required.

[0006] In view of the above circumstances, the present invention provides a method for easily and sufficiently incorporating an arbitrary component into a polarizing film. The present invention aims to provide a method for producing a polarizing film having a good polarization degree.

[0007] The present invention also relates to a method for producing a polarizing film using the polarizing film obtained by the above-mentioned method for producing a polarizing film. The present invention aims to provide a manufacturing method thereof. [Means for solving the problem]

[0008] That is, the present invention is a method for producing a polarizing film, comprising the steps of: While conveying the polyvinyl alcohol film in the longitudinal direction, at least a dyeing process is performed on the polyvinyl alcohol film. (I-1) a step of producing a water-containing polarizing film by carrying out a stretching step, a crosslinking step, and a stretching step; and applying a liquid to the obtained water-containing polarizing film in a state where the moisture content of the polarizing film is X% by weight or more. (I-2) producing a polarizing film impregnated with the components in the liquid; The polarizing film impregnated with the components in the obtained liquid is subjected to a drying process to produce a dried polarizing film. The formula (1): X (wt%) / thickness of the polarizing film after drying (μ m)>1 (wherein, X is 10 or more and 70 or less). The present invention relates to a method for producing the above-mentioned compound.

[0009] The present invention also relates to a method for producing a polarizing film, comprising the steps of: A polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin is formed to prepare a laminate. and a step (II-0) of conveying the obtained laminate in the longitudinal direction while applying a small amount of the At least, the fabric is subjected to an air-assisted stretching process, a dyeing process, and an underwater stretching process to obtain a water-resistant fabric. and producing a laminate having a polarizing film containing the resulting water-containing A liquid is applied to a laminate having a polarizing film while the moisture content of the polarizing film is at least Y% by weight. A step (II-2) of producing a laminate having a polarizing film impregnated with a component in a liquid by carrying out the steps ) and subjecting the laminate having the polarizing film impregnated with the components in the liquid obtained to a drying process. and a step (II-3) of producing a polarizing film after drying, The thickness (μm) of the polarizing film after drying is greater than 1 (where Y is 10 or more and 70 or less). The present invention relates to a method for producing a polarizing film that satisfies the above conditions.

[0010] The present invention also provides a method for producing a polarizing film, comprising the steps of: applying an adhesive to at least one surface of the polarizing film obtained by the method for producing a polarizing film; A method for producing a polarizing film, comprising the step of laminating a transparent protective film through a layer. do. Effect of the Invention

[0011] Although the details of the mechanism of action of the method for producing the polarizing film of the present invention are unclear, However, the present invention should not be interpreted as being limited to this mechanism of action. It's not necessary.

[0012] In the method for producing a polarizing film of the present invention, the polyvinyl alcohol film is not transported in the longitudinal direction. The polyvinyl alcohol film is then subjected to at least a dyeing process, a crosslinking process, and and a stretching step to produce a water-containing polarizing film (I-1); A step of applying a liquid to a polarizing film having a moisture content of X% by weight or more is performed. The method includes the steps of: (I-2) producing a polarizing film impregnated with a component in a liquid; and (I-3) forming a polarizing film impregnated with the component in the liquid. A step (I-3) of drying the polarizing film impregnated with the component to produce a dried polarizing film. and the formula (1): X (wt%) / thickness (μm) of the polarizing film after drying>1 (formula (1) In the above, X is 10 or more and 70 or less. The method for producing the membrane is to apply a polyvinyl alcohol-based resin to one side of a long thermoplastic resin substrate. A step (II-0) of preparing a laminate by forming a polyvinyl alcohol-based resin layer containing the polyvinyl alcohol-based resin; The laminate is subjected to at least an auxiliary air-stretching process while being conveyed in the longitudinal direction. The laminate having a water-containing polarizing film is then subjected to a dyeing process and an underwater stretching process. and a step (II-1) of producing a laminate having a polarizing film containing water, and When the moisture content of the film is Y% by weight or more, a liquid is applied to the film, and the components in the liquid are A step (II-2) of producing a laminate having an impregnated polarizing film, and A process for producing a dried polarizing film by subjecting the laminate having the impregnated polarizing film to a drying treatment process. The formula (3): Y (wt%) / thickness of the polarizing film after drying (μm )>1 (where Y is 10 or more and 70 or less). In the method for producing a polarizing film, a polyvinyl alcohol film is subjected to at least a dyeing process, a crosslinking process, and a After the crosslinking and stretching steps, the film is then dried. In the manufacturing method of the light-shielding film, a polyvinyl alcohol resin is applied to one side of a long thermoplastic resin substrate. forming a polyvinyl alcohol-based resin layer containing the compound, to prepare a laminate; The body is subjected to at least an air-assisted stretching process, a dyeing process, and an underwater stretching process. On the other hand, in the method for producing a polarizing film of the present invention, As described above, a water-containing polarizing film or a laminate having a water-containing polarizing film is produced. The method for producing a polarizing film of the present invention satisfies the condition of formula (1) or (3) above, so that In the liquid application process, any component contained in the liquid can be simply added to the polarizing film containing water. The impregnation can be performed conveniently and sufficiently, and a polarizing film having a good polarization degree can be produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Method of manufacturing polarizing film> In the method for producing a polarizing film of the present invention, the polyvinyl alcohol film is not transported in the longitudinal direction. The polyvinyl alcohol film is then subjected to at least a dyeing process, a crosslinking process, and and a stretching step to produce a water-containing polarizing film (I-1); A step of applying a liquid to a polarizing film having a moisture content of X% by weight or more is performed. The method includes the steps of: (I-2) producing a polarizing film impregnated with a component in a liquid; and (I-3) forming a polarizing film impregnated with the component in the liquid. A step (I-3) of drying the polarizing film impregnated with the component to produce a dried polarizing film. and the formula (1): X (wt%) / thickness (μm) of the polarizing film after drying>1 (formula (1) In the above, X is greater than or equal to 10 and less than or equal to 70.

[0014] <Step (I-1) of Producing a Water-Containing Polarizing Film> In the method for producing a polarizing film of the present invention, the polyvinyl alcohol film is not transported in the longitudinal direction. The polyvinyl alcohol film is then subjected to at least a dyeing process, a crosslinking process, and and a stretching step (I-1) to produce a water-containing polarizing film.

[0015] The polyvinyl alcohol (PVA) film has translucency in the visible light region. Any material that disperses and adsorbs dichroic substances such as iodine and dichroic dyes can be used without any particular limitations. In addition, the PVA film that is usually used as the raw material has a thickness of about 1 to 100 μm. It is preferable that the thickness is about 1 to 50 μm, and more preferable that the width is 100 to 5000 mm. It is preferable that the amount is about 100%.

[0016] The material of the polyvinyl alcohol-based film is polyvinyl alcohol or The derivatives of polyvinyl alcohol include, for example, polyvinyl formal, polyvinyl acetal; olefins such as ethylene and propylene; acrylic Unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, and their alkyl esters, The polyvinyl alcohol may be modified with acrylamide or the like. The degree is preferably about 100 to 10,000, and more preferably about 1,000 to 10,000. It is more preferable that the molecular weight is about 1,500 to 4,500, and further preferably about 1,500 to 4,500. The polyvinyl alcohol preferably has a degree of saponification of about 80 to 100 mol %. It is preferable that the average polymerization amount is about 95 mol % to 99.95 mol %. The degree of saponification and the degree of hydrolysis can be determined in accordance with JIS K 6726.

[0017] The polyvinyl alcohol film contains additives such as plasticizers and surfactants. Examples of the plasticizer include glycerin, diglycerin, and triglycerin. Polyols such as ethylene glycol, propylene glycol, and polyethylene glycol The amount of the additives used is not particularly limited. For example, The content of the polyvinyl alcohol in the polyvinyl alcohol film is preferably about 20% by weight or less.

[0018] <Dyeing process> The dyeing step is a treatment step of immersing a polyvinyl alcohol film in a dye bath. Polyvinyl alcohol film is adsorbed with iodine or dichroic dyes. The dye solution is preferably an aqueous iodine solution, It contains iodine and an iodide as a dissolving agent. Potassium, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, iodine Examples include lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Among these, potassium iodide is preferable.

[0019] The concentration of iodine in the dye bath is preferably about 0.01 to 1% by weight, and 0. It is more preferable that the concentration of the iodide in the dye bath is about 0.2 to 0.5% by weight. The content is preferably about 0.01 to 10% by weight, and more preferably about 0.05 to 5% by weight. is more preferable.

[0020] The temperature of the dye bath is preferably about 10 to 50° C., and more preferably about 15 to 45° C. It is more preferable that the immersion time in the dye bath is about 10 minutes. The degree of dyeing of the dye is affected by the temperature of the dye bath, so it cannot be determined in general, but it is recommended to use a temperature range of 10 to 30 It is preferable that the time is about 0 seconds, and more preferable that the time is about 20 to 240 seconds. The staining step may be carried out once or may be carried out multiple times as necessary.

[0021] <Crosslinking process> The crosslinking step is a step of crosslinking the polyvinyl alcohol-based film dyed in the dyeing step. This is a treatment process in which the material is immersed in a treatment bath (crosslinking bath) that contains a boron compound. The vinyl alcohol film crosslinks, and the iodine or dye molecules are attached to the crosslinked structure. Examples of the boron compound include boric acid, borate, and borax. The crosslinking bath is generally an aqueous solution, but may be, for example, an organic solvent miscible with water or The crosslinking bath may be a mixed solution of potassium iodide and water. It can include.

[0022] The concentration of the boron compound in the crosslinking bath is preferably about 1 to 15% by weight. It is more preferably about 1.5 to 10% by weight, and even more preferably about 2 to 5% by weight. In addition, when an iodide such as potassium iodide is used in the crosslinking bath, The concentration of the iodide such as potassium iodide in the bath is preferably about 1 to 15% by weight. It is more preferable that the content is about 1.5 to 10% by weight.

[0023] The temperature of the crosslinking bath is preferably about 20 to 70° C., and more preferably about 30 to 60° C. It is more preferable that the immersion time in the crosslinking bath is The degree of crosslinking of the film is affected by the temperature of the crosslinking bath, so it cannot be determined in general terms. The time is preferably about 2 seconds, and more preferably about 10 to 200 seconds. The crosslinking step may be carried out only once, or may be carried out multiple times as necessary.

[0024] <Stretching process> The stretching step is a step of stretching a polyvinyl alcohol-based film at a predetermined stretch ratio in at least one direction. In general, the polyvinyl alcohol film is stretched in the conveying direction ( The stretching method is not particularly limited, and may be a wet stretching method or a dry stretching method. The stretching step may be carried out only once, or may be carried out multiple times as necessary. The stretching step may be carried out at any stage in the production of the polarizing film. good.

[0025] The treatment bath (stretching bath) in the wet stretching method is usually water or a water-miscible active ingredient. The stretching bath may be a mixture of organic solvent and water. The stretching bath may contain an iodide such as potassium iodide. In this case, the concentration of the iodide such as potassium iodide in the drawing bath is about 1 to 15% by weight. It is preferable that the concentration is about 2 to 10% by weight. The stretching bath may contain the boron compound to improve the degree of crosslinking. In this case, The concentration of the boron compound in the drawing bath is preferably about 1 to 15% by weight, It is more preferable that the content is about 1.5 to 10% by weight.

[0026] The temperature of the stretching bath is preferably about 25 to 80° C., and more preferably about 40 to 75° C. It is more preferable that the immersion time in the stretching bath is set to 100 minutes. The degree of stretching of the film is affected by the temperature of the stretching bath, so it cannot be determined in general. It is preferable that the time is about 0 seconds, and more preferable that the time is about 30 to 500 seconds. The stretching treatment in the wet stretching method includes the dyeing step, the crosslinking step, and the swelling step described later. The above-mentioned treatment step may be carried out together with one or more of the treatment steps described below, and the washing step described later.

[0027] Examples of the dry stretching method include a roll-to-roll stretching method, a heated roll stretching method, and a compression stretching method. The dry stretching method may be carried out together with the drying step described below. .

[0028] The total stretching ratio (accumulated stretching ratio) applied to the polyvinyl alcohol film is The amount can be appropriately set depending on the purpose, but it is preferably about 2 to 7 times, and more preferably about 3 to 6.8 times. It is more preferable that the ratio is about 3.5 to 6.5 times, and further more preferable that the ratio is about 3.5 to 6.5 times.

[0029] In the step of producing the water-containing polarizing film, In addition to the dyeing step, the crosslinking step, and the stretching step, a swelling step may be performed. A washing step may be carried out.

[0030] <Swelling process> The swelling step is a treatment step of immersing a polyvinyl alcohol film in a swelling bath. It can remove dirt and blocking agents from the surface of polyvinyl alcohol-based films. In addition, uneven dyeing can be suppressed by swelling the polyvinyl alcohol film. The wetting bath is usually a medium whose main component is water, such as distilled water or pure water. In accordance with a conventional method, a surfactant, alcohol, etc. may be appropriately added.

[0031] The temperature of the swelling bath is preferably about 10 to 60° C., and more preferably about 15 to 45° C. It is more preferable that the immersion time in the swelling bath is The degree of swelling of the film is affected by the temperature of the swelling bath, so it cannot be determined in general. It is preferable that the time is about 20 seconds, and more preferable that the time is about 10 to 200 seconds. The swelling step may be carried out only once, or may be carried out multiple times as necessary.

[0032] <Cleaning process> The washing step is a treatment step of immersing the polyvinyl alcohol film in a washing bath. The cleaning method can remove foreign matter remaining on the surface of the polyvinyl alcohol film. The bath is usually a medium whose main component is water, such as water, distilled water, or pure water. Iodides such as potassium iodide can be used in the bath. In this case, iodide is present in the cleaning bath. The concentration of the potassium iodide, such as potassium iodide, is preferably about 1 to 10% by weight, and more preferably 2 to 4 times. It is more preferable that the content is about 1.6 to 3.8% by weight. It is nice.

[0033] The temperature of the cleaning bath is preferably about 5 to 50° C., and more preferably about 10 to 40° C. It is more preferable that the temperature of the cleaning bath is about 15 to 30° C. The immersion time in the cleaning bath is determined based on the effect of the temperature of the cleaning bath on the degree of cleaning of the polyvinyl alcohol-based film. The time cannot be determined in general because the temperature is high, but it is preferable to set the time to about 1 to 100 seconds, and 2 to 50 seconds. It is more preferable that the time is about 2 seconds, and further more preferable that the time is about 3 to 20 seconds. The swelling step may be carried out only once, or may be carried out multiple times as necessary.

[0034] Furthermore, the swelling process, the dyeing process, the crosslinking process, the stretching process and the washing process Each treatment bath in the process contains additives such as zinc salts, pH adjusters, pH buffers, and other salts. The zinc salt may contain, for example, a halogen salt such as zinc chloride or zinc iodide. Examples of the pH adjuster include zinc nitrate, zinc sulfate, zinc acetate, and other inorganic zinc salts. For example, strong acids such as hydrochloric acid, sulfuric acid, and nitric acid, and strong bases such as sodium hydroxide and potassium hydroxide. Examples of the pH buffer include carboxylic acids such as acetic acid, oxalic acid, and citric acid. Examples of the weak acids include inorganic acids and their salts, such as phosphoric acid and carbonic acid, and inorganic weak acids and their salts. Other salts include, for example, chlorides such as sodium chloride, potassium chloride, and barium chloride; Nitrates such as sodium nitrate and potassium nitrate, sodium sulfate and potassium sulfate Examples include sulfates, and salts of alkali metals and alkaline earth metals.

[0035] <Process (I-2) for producing a polarizing film impregnated with liquid components> The method for producing a polarizing film of the present invention comprises the steps of: In a state where the content of the liquid is X% by weight or more, a liquid coating process is carried out to form a biased surface in which the liquid has permeated the surface. The method includes a step (I-2) of producing a light-transmitting film. Here, the components in the liquid are usually contained in a solution. The solute is a substance that can be dissolved or dispersed in a solvent. The mixture may be any of a gaseous substance, a liquid substance, and a solid substance. However, in the case of a liquid substance (for example, under conditions of 25°C and 1 atm), the liquid substance itself (liquid substance itself) may be a liquid and a component in a liquid.

[0036] In the step (I-2), the components contained in the liquid are easily impregnated, and the polarizing film is From the viewpoint of making it easier for the liquid to penetrate into the liquid, the moisture content of the polarizing film (X% by weight) is set to 20% by weight. % or more, and the moisture content of the polarizing film is preferably 22% by weight or more. It is more preferable that the moisture content of the polarizing film is 25% by weight or more. From the viewpoint of preventing wrinkles during transportation, the moisture content of the polarizing film is preferably 65% ​​by weight or more. It is preferable that the moisture content of the polarizing film is 60% by weight or less. It is more preferable that

[0037] The coating method in the step of applying the liquid may be a conventional coating method. For example, roll coating, spin coating, wire bar coating, and dip coating can be used. Coating method, die coating method, curtain coating method, spray coating method, knife coating method (coating method) The coating method of the polarizing film is one-sided. It may be either one or both sides.

[0038] The component in the liquid is water-soluble from the viewpoint of easily impregnating the component into the water-containing polarizing film. The water-soluble compound may be a compound having a water content of 100 g per 100 g of water at 25°C. It is said to have a solubility of 1 g or more.

[0039] The components in the liquid include, for example, zinc salts (zinc halides such as zinc chloride and zinc iodide) Lead; inorganic zinc salts such as zinc sulfate and zinc acetate; organic titanium compounds (titanium alkoxides, Titanium chelate, titanium chelate ammonium salt, titanium chelate acylate, etc.), organic Zirconium (zirconyl alkoxide, zirconyl chelate, zirconyl chelate amine) monium salts, zirconyl acylate), alkali metal salts, alkaline earth metal salts, metal halide salts Examples of such compounds include genides.

[0040] In addition, the components in the liquid include a compound having a radical scavenging function (a radical scavenger The compound having the radical scavenging function is preferably a compound having a radical scavenging function. Alcohol captures radicals generated by heating and suppresses polyenation, making it possible to use it as a polarizing film. The compound having a radical scavenging function can improve the heat durability of the poly From the viewpoint of easily suppressing the ene formation, for example, nitroxy radicals or nitroxides It is preferable that the compound has a group.

[0041] Examples of the compound having a nitroxy radical or a nitroxide group include the following: Examples include compounds having an organic group of the structure below. [ka] (In general formula (1), R 1 represents an oxy radical, and R 2 From R 5 is independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and n is 0 or 1. In general formula (1), the left side of the dotted line represents an arbitrary organic group.

[0042] The compounds having the above organic group include, for example, those represented by the following general formulas (2) to (5): Compounds such as those mentioned above are also enumerated. [ka] (In general formula (2), R 1 ~R 5 , and n are the same as above, and R 6 is a hydrogen atom, and represents an alkyl group, an acyl group, or an aryl group having 1 to 10 carbon atoms. [ka] (In general formula (3), R 1 From R 5 , and n are the same as above, and R 7 and R 8 teeth, Independently, a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an acyl group, or an aryl group Represents a aryl group. [ka] (In general formula (4), R 1 From R 5 , and n are the same as above, and R 9 From R 11 teeth, Independently, a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an acyl group, an amino group, represents an alkoxy group, a hydroxy group, or an aryl group. [ka] (In general formula (5), R 1 From R 5 , and n are the same as above, and R 12 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, an amino group, an alkoxy group, a hydroxy group, or an aryl group.

[0043] In the general formulas (1) to (5), R 2 From R 5 From the viewpoint of availability, The alkyl group has preferably 1 to 6 carbon atoms, and more preferably 1 to 3 carbon atoms. In addition, in the general formula (2), from the viewpoint of availability, R 6 is a hydrogen atom, Alternatively, it is preferably an alkyl group having 1 to 10 carbon atoms, and is preferably a hydrogen atom. In addition, in the general formula (3), R 7 and R 8 is Preferably, each of the alkyl groups is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. In addition, in the general formula (4), from the viewpoint of availability, R 9 From R 11 is preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. In addition, in the general formula (5), from the viewpoint of availability, R 12 is a hydroxy group, In the general formulae (1) to (5), n is preferably an amino group or an alkoxy group. From the viewpoint of availability, 1 is preferable.

[0044] The compound having a nitroxy radical or a nitroxide group may, for example, be Examples include the following compounds: [ka] In the general formula (6), R is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an acyl group, represents a group, or an aryl group. [ka] [ka]

[0045] In addition, the components in the liquid include compounds having a cross-linking function (also called cross-linking agents). The compound having a crosslinking function reacts with the hydroxyl group of the polyvinyl alcohol of the polarizing film. By using the crosslinking function, a crosslinked structure is formed, and the durability of the polarizing film against moisture can be improved. From the viewpoint of improving durability against moisture, the compound having an isocyanate group, an isocyanate group, Derivative functional groups, epoxy groups, carbonyl groups, aziridine rings, vinyl ether groups, vinyl In addition to organic compounds with arylsulfone and oxazoline groups, organic titanium compounds (titanium arsenide compounds) Koxide, titanium chelate, titanium chelate ammonium salt, titanium chelate acylate etc.)

[0046] In addition, the components in the liquid include compounds that have the function of imparting plasticity (also called plasticizers). The compound having a function of imparting plasticity can be used to impart plasticity to a polarizing film. This reduces quality defects such as dents caused by the pressing force. Examples of compounds having the function of providing the function include ethylene glycol, polyethylene glycol, and the like. Examples of such glycol derivatives include ethylene glycol, glycerin, etc.

[0047] In addition, the components in the liquid include dye compounds (also called dyes). The dye-based compound can impart properties such as hue adjustment and pattern printing to the polarizing film. Examples of compounds include azo compounds, anthraquinone compounds, and quinophthalone compounds. Can be obtained.

[0048] The liquid cannot be determined in general because it is affected by the above-mentioned application (coating) method, but From the viewpoint of allowing the components in the liquid to penetrate well, the concentration of the components in the liquid is set to 0.1% by weight or less. It is preferable that the content of the cation exchange resin is 1.0% by weight or more, and more preferable that the content of the cation exchange resin is 1.0% by weight or more, and From the viewpoint of preventing quality defects due to precipitation of the above components, the content is preferably 30% by weight or less. It is preferably 20% by weight or less.

[0049] The solvent may be water, methanol, ethanol, ethylene glycol, polyethylene glycol, other ethylene glycol derivatives, glycerin, dimethyl sulfoxide, etc. Water-soluble solvents and the like.

[0050] The time from the end of the step (I-1) to the start of the step (I-2) (polarization in actual production) The film transport time is determined from the viewpoint of maintaining the moisture contained in the water-containing polarizing film or From the viewpoint of productivity, the temperature is about 15°C to 35°C, preferably about 20°C to 30°C. Preferably, the time is 300 seconds or less, more preferably, 180 seconds or less, and more preferably, 60 seconds or less. It is more preferable that the time is less than 10 seconds, and even more preferable that the time is less than 10 seconds.

[0051] In the step (I-2), if necessary, a liquid may be applied to the polarizing film containing water. After the step of impregnating the substrate with a part of the liquid, a step of removing the remaining liquid may be performed. Methods for removing liquid include wiping with a rag or sponge roll, or suction. These include the removal method using a blower, a method using a bar or a gravure roll to scrape off the dust. can be done.

[0052] In the step (I-2), the water-containing polarizing film satisfies the condition of the following formula (a): It is preferable that the above-mentioned condition is satisfied. By setting the boron content in the polarizing film, the components in the liquid can be efficiently permeated. It is possible to do so. Formula (a): A (weight%)<0.08×B(μm)+3.3 (In formula (a), A is the content (wt%) of boron in the polarizing film containing water, and B is The thickness of the polarizing film after drying (μm).

[0053] <Process for Producing Dried Polarizing Film (I-3)> The method for producing a polarizing film of the present invention comprises the steps of: drying the polarizing film impregnated with the components in the liquid obtained above; The method includes a step (I-3) of carrying out a process to produce a polarizing film after drying.

[0054] The drying step is to dry the polarizing film impregnated with the components in the liquid obtained above to obtain a polarizing film. The drying step is a step of obtaining a polarizing film having a desired moisture content. For example, natural drying, air drying, and heat drying can be used.

[0055] The drying temperature is preferably about 20 to 150° C., and more preferably about 25 to 100° C. It is more preferable that the drying time is set to a value that is proportional to the drying temperature. It is difficult to determine the exact time because it is influenced by the temperature, but it is preferable to set the temperature to about 10 to 600 seconds. It is more preferable that the drying process is performed for about 30 to 300 seconds. This may be carried out multiple times if necessary.

[0056] The dried polarizing film is prevented from suffering quality defects such as dents due to loss of plasticity. From this viewpoint, the moisture content is preferably 10% by weight or more, and more preferably 12% by weight or more. From the viewpoint of improving optical properties such as the degree of polarization, it is more preferable that the moisture content is 20 times or less. It is preferable that the content of the cellulose acetate is 16% by weight or less, and more preferable that the content of the cellulose acetate is 16% by weight or less. In the case of a dried polarizing film with a thickness of about 8 μm or less, as described below, the plasticity disappears. From the viewpoint of preventing quality defects such as dents due to loss of moisture, the moisture content is set to 2% by weight or more. It is preferable that the content of the fluorine-containing compound is 3% by weight or more, and more preferable that the content of the fluorine-containing compound is 3% by weight or more. From the viewpoint of improving the characteristics, the moisture content is preferably 20% by weight or less, and more preferably 10% by weight or less. % or less is more preferable.

[0057] The thickness of the polarizing film after drying is preferably about 1 to 30 μm, and more preferably 5 to 25 μm. It is more preferable that the thickness is about 1 μm, and further preferably 5 to 20 μm. In order to obtain a polarizing film having a thickness of about 8 μm or less after drying, the above polyvinyl alcohol-based film is The film is a laminate including a polyvinyl alcohol-based resin layer formed on a thermoplastic resin substrate. The following method for producing a thin polarizing film using a layered product can be applied.

[0058] The method for producing a polarizing film of the present invention is based on the formula (1): X (wt %) / thickness of the polarizing film after drying The condition that the thickness (μm) is greater than 1 is satisfied, preferably the formula (1) is greater than 1.2, and more preferably the formula (1) is greater than 1.2. is equation (1)>1.5.

[0059] In addition, the method for producing a polarizing film of the present invention is capable of increasing the degree of polarization when the film is in a polarizing film state. From this viewpoint, the above-mentioned X (wt%)−the moisture content (wt%) of the polarizing film after drying> It is preferable that the condition (2) is 0 (wt%), and the condition (2) is > 2 (wt%). It is more preferable that the formula (2) is greater than 5 (wt %).

[0060] <Manufacturing method of polarizing film (thin polarizing film)> The manufacturing method for polarizing films (thin polarizing films) is to attach a polyvinyl chloride film to one side of a long thermoplastic resin substrate. forming a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin to prepare a laminate; Step (II-0) and conveying the obtained laminate in the longitudinal direction, at least The water-containing yarn is also subjected to an air-assisted stretching process, a dyeing process, and an underwater stretching process. (II-1) producing a laminate having a polarizing film, and (II-2) producing the polarizing film containing water. A step of applying a liquid to the laminate having the polarizing film in a state where the moisture content of the polarizing film is Y% by weight or more. (II-2) carrying out the above-mentioned step to produce a laminate having a polarizing film impregnated with a component in the liquid; The laminate having the polarizing film impregnated with the components in the liquid is subjected to a drying treatment step to dry the laminate. The process (II-3) for producing a polarizing film is carried out according to the formula (3): Y (wt%) / the drying The thickness (μm) of the polarizing film after the polarizing process is greater than 1 (where Y is 10 or more and 70 or less). Meet the conditions.

[0061] <Step of preparing laminate (II-0)> The method for producing the polarizing film (thin polarizing film) of the present invention is to form a film on one side of a long thermoplastic resin substrate, Polyvinyl alcohol resin layer (P) containing polyvinyl alcohol resin (PVA resin) The method includes a step (II-0) of forming a laminate by forming a VA-based resin layer.

[0062] The laminate can be prepared by any suitable method. For example, The method comprises applying a coating solution containing the PVA resin to the surface of a plastic resin substrate and drying the coating solution. The thickness of the thermoplastic resin substrate is preferably about 20 to 300 μm. The thickness of the PVA-based resin layer is preferably about 30 to 200 μm. It is preferably about 10 μm or less, and more preferably about 3 to 20 μm.

[0063] The thermoplastic resin substrate absorbs water to greatly reduce the stretching stress and can be stretched at a high ratio. From the viewpoint of being able to absorb water, the water absorption rate is preferably about 0.2% or more, and more preferably about 0.3% or more. On the other hand, the thermoplastic resin substrate is preferably a substrate having a size of 100 mm or more. To prevent problems such as deterioration of the appearance of the obtained polarizing film due to a significant decrease in process stability. From the viewpoint of achieving this, the water absorption rate is preferably about 3% or less, and more preferably about 1% or less. The water absorption rate is preferably, for example, The water absorption rate can be adjusted by introducing a functional group. This value can be calculated in accordance with the above.

[0064] The thermoplastic resin substrate is capable of suppressing crystallization of the PVA-based resin layer while improving the stretchability of the laminate. From the viewpoint of being able to sufficiently secure the glass transition temperature (Tg) of about 120°C or less. Furthermore, it is preferable that the plasticization of the thermoplastic resin substrate by water and the underwater stretching are performed well. Considering this, it is more preferable that the glass transition temperature (Tg) is about 100° C. or less. It is preferable that the temperature is about 90° C. or less, and more preferable that the temperature is about 90° C. or less. The transition temperature is the temperature at which defects such as deformation of the thermoplastic resin substrate occur when the coating liquid is applied and dried. From the viewpoint of preventing this and producing a good laminate, the temperature is set to about 60° C. or higher. The glass transition temperature is preferably determined by, for example, changing the constituent material of the thermoplastic resin substrate. The above can be adjusted by introducing a functional group into the crystallization material or by heating the crystallization material. The glass transition temperature (Tg) is a value determined in accordance with JIS K 7121.

[0065] As the constituent material of the thermoplastic resin substrate, any appropriate thermoplastic resin can be adopted. The thermoplastic resin may be, for example, an ester such as a polyethylene terephthalate resin. olefin resins such as norbornene resins, cycloolefin resins such as polypropylene Examples of the resins include acrylate resins, polyamide resins, polycarbonate resins, and copolymer resins thereof. Among these, norbornene resins and amorphous polyethylene terephthalate are The thermoplastic resin substrate is preferably a tallow resin, and has excellent stretchability. From the viewpoint of suppressing crystallization during stretching, amorphous (non-crystalline) polyethylene terephthalate Amorphous (non-crystalline) polyethylene terephthalate-based resins are preferably used. As dicarboxylic acids, isophthalic acid and / or cyclohexanedicarboxylic acid Copolymers containing cyclohexanedimethanol and diethylene glycol as glycols Copolymers containing ethylenediaminetetraacetate are also suitable.

[0066] The thermoplastic resin substrate is subjected to a surface treatment (e.g., corona treatment) before the PVA-based resin layer is formed. Alternatively, an easy-adhesion layer may be formed on the thermoplastic resin substrate. By carrying out such a treatment, it is possible to improve the adhesion between the thermoplastic resin substrate and the PVA-based resin layer. The thermoplastic resin substrate may be stretched before the PVA-based resin layer is formed. It may be possible.

[0067] The coating liquid is a solution in which a PVA-based resin is dissolved in a solvent. For example, water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methyl Tylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, Examples of the amine include amines such as ethylenediamine and diethylenetriamine, and water is preferred. The PVA resin of the coating liquid may be used alone or in combination of two or more thereof. The oil concentration is determined from the viewpoint of forming a uniform coating film that is in close contact with the thermoplastic resin substrate. The amount is preferably about 3 to 20 parts by weight based on 100 parts by weight of the solvent.

[0068] In order to improve the orientation of polyvinyl alcohol molecules by stretching, the coating liquid It is preferable that a halide is blended. The halide may be any suitable compound. Any suitable halide may be employed, such as iodide and sodium chloride. Examples of the iodide include potassium iodide, sodium iodide, and lithium iodide. The concentration of the halide in the coating solution is preferably P The amount is preferably about 5 to 20 parts by weight, and more preferably about 10 to 10 parts by weight, based on 100 parts by weight of the VA resin. It is more preferable that the amount is about 5 parts by weight.

[0069] The coating liquid may contain additives. Examples of the additives include ethyl acetate. Plasticizers such as polyethylene glycol and glycerin; surfactants such as nonionic surfactants. can be.

[0070] As a method for applying the coating liquid, any appropriate method can be adopted. For example, Roll coating method, spin coating method, wire bar coating method, dip coating method, die coating method These include the curtain coat method, spray coat method, and knife coat method (comma coat method, etc.). The drying temperature of the coating liquid is preferably about 50° C. or higher.

[0071] <Step (II-1) of Producing a Laminate Having a Water-Containing Polarizing Film> The method for producing the polarizing film (thin polarizing film) of the present invention comprises carrying the laminate obtained above in the longitudinal direction. While conveying the laminate, the laminate is subjected to at least an air-assisted stretching process, a dyeing process, and A process for producing a laminate having a water-containing polarizing film by performing an underwater stretching process (II- 1) is included.

[0072] The in-air auxiliary stretching process is performed while suppressing crystallization of the thermoplastic resin substrate. Therefore, the laminate can be stretched at a high ratio. The stretching method may be fixed end stretching (for example, a method of stretching using a tenter stretching machine) or self-stretching. End-drawing (for example, a method of uniaxially drawing the laminate by passing it between rolls having different peripheral speeds) may also be used. However, from the viewpoint of obtaining high optical properties, free end stretching is preferred.

[0073] The stretching ratio in the auxiliary air-stretching process is preferably about 2 to 3.5 times. The in-air auxiliary stretching process may be carried out in one step or in multiple steps. When the stretching is performed in a single step, the stretching ratio is the product of the stretching ratios in each step.

[0074] The stretching temperature in the auxiliary air stretching process depends on the material of the thermoplastic resin substrate, the stretching method, and the like. It can be set to any appropriate value depending on the formula, etc. For example, The temperature is preferably equal to or higher than the glass transition temperature (Tg), and is preferably equal to or higher than the glass transition temperature (Tg) + 10°C. It is more preferable that the temperature is equal to or higher than the glass transition temperature (Tg)+15° C. On the other hand, the upper limit of the stretching temperature is set to a value that suppresses the crystallization of the PVA resin from proceeding too rapidly. This suppresses defects caused by crystallization (for example, preventing the orientation of the PVA-based resin layer due to stretching). From the viewpoint of being able to heat the material, the temperature is preferably about 170°C.

[0075] If necessary, after the air-assisted stretching process, before the dyeing process or the underwater stretching process The insolubilization treatment step may be typically carried out using an aqueous boric acid solution. The insolubilization process is carried out by immersing the PVA resin layer in the insolubilization process. This gives water resistance to the resin layer, and prevents the orientation of the PVA from decreasing when immersed in water. The concentration of the boric acid aqueous solution is about 1 to 5 parts by weight per 100 parts by weight of water. The liquid temperature of the insolubilization bath is preferably about 20 to 50°C.

[0076] The dyeing process is carried out by dyeing the PVA-based resin layer with iodine. For example, a method of immersing a PVA-based resin layer (laminate) in a dye solution containing iodine is used. A method of applying the dye solution to a PVA-based resin layer, a method of spraying the dye solution onto a PVA-based resin layer The method includes immersing a PVA resin layer (laminate) in a dye solution containing iodine. preferable.

[0077] The amount of iodine in the dye bath is 0.05 to 0.5 parts by weight per 100 parts by weight of water. In order to increase the solubility of iodine in water, an iodine aqueous solution is preferably used. The amount of the iodide to be mixed is preferably 100 parts by weight of water. It is preferably about 0.1 to 10 parts by weight, and more preferably about 0.3 to 5 parts by weight. The temperature of the dye bath is preferably 20 to 50° C. in order to suppress dissolution of the PVA resin. The immersion time is preferably about 10 minutes from the viewpoint of ensuring the transmittance of the PVA-based resin layer. Therefore, it is preferably about 5 seconds to 5 minutes, and more preferably about 30 seconds to 90 seconds. In order to obtain a polarizing film having good optical properties, the iodine and The ratio of the content of iodide to the content of iodide is preferably about 1:5 to 1:20, more preferably about 1:5 to 1: A value of about 10 is more preferable.

[0078] If necessary, a crosslinking process may be performed after the dyeing process and before the underwater stretching process. The crosslinking step may typically include immersing the PVA resin layer in an aqueous solution of boric acid. The crosslinking process provides the PVA resin layer with water resistance. In the subsequent underwater stretching, it is possible to prevent a decrease in the orientation of the PVA when the film is immersed in hot water. The boric acid concentration of the aqueous boric acid solution is about 1 to 5 parts by weight per 100 parts by weight of water. In addition, when a crosslinking treatment step is performed, the crosslinking bath further contains the iodide. It is preferable that the iodide is adsorbed in the PVA resin layer by blending the iodide. The amount of the iodide to be blended is 100 parts by weight of water. The liquid temperature of the crosslinking bath (aqueous boric acid solution) is preferably 20 to 5 parts by weight. A temperature of about 50°C is preferable.

[0079] The underwater stretching step is carried out by immersing the laminate in a stretching bath. For example, the glass transition temperature of the thermoplastic resin substrate or the PVA resin layer (typically, about 80° C.) ) can be stretched at a lower temperature than that of the conventional polymer film, and the PVA resin layer can be stretched at a high magnification while suppressing its crystallization. The stretching method in the underwater stretching process can be fixed end stretching (for example, ten The stretching method may be a method of stretching the film using a rotor stretching machine, or a method of stretching the film using a free end stretching machine (for example, a method of stretching the film using a rotor stretching machine with different peripheral speeds). However, from the viewpoint of obtaining high optical properties, Free end drawing is preferred.

[0080] The underwater stretching step is carried out by immersing the laminate in an aqueous boric acid solution (in an aqueous boric acid solution By using an aqueous solution of boric acid as the stretching bath, the PVA resin layer can be stretched. It can provide the rigidity to withstand the tension that is sometimes applied, and the water resistance to prevent dissolution in water. The concentration of boric acid in the aqueous acid solution is preferably 1 to 10 parts by weight per 100 parts by weight of water. The amount of the boric acid in the stretching bath (aqueous boric acid solution) is preferably 2.5 to 6 parts by weight. The liquid temperature of the stretching bath is preferably about 40 to 85° C. The temperature is preferably about 60 to 75° C. The immersion time of the laminate in the stretching bath is 1 It is preferable that the time be about 5 seconds to 5 minutes.

[0081] The stretching ratio in the underwater stretching process is preferably about 1.5 times or more, It is more preferable that the amount is about three times or more.

[0082] The total stretching ratio of the laminate is preferably about 5 times or more the original length of the laminate. It is preferable that the ratio is about 5.5 times or more.

[0083] It is preferable to carry out a washing process after the underwater stretching process. Typically, this is done by immersing the PVA resin layer in an aqueous potassium iodide solution.

[0084] Furthermore, the dyeing process, the underwater stretching process, the insolubilization process, and the crosslinking process The treatment baths in the treatment step and the cleaning step contain zinc salt, pH adjuster, pH buffer, etc. The zinc salt may contain additives such as salts. zinc halides such as zinc chloride and zinc iodide; inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of the pH adjuster include strong acids such as hydrochloric acid, sulfuric acid, and nitric acid, and sodium hydroxide. Examples of the pH buffer include strong bases such as acetic acid, Carboxylic acids such as oxalic acid and citric acid and their salts, inorganic weak acids such as phosphoric acid and carbonic acid, Examples of the other salts include sodium chloride, potassium chloride, and salts thereof. chlorides such as barium chloride, nitrates such as sodium nitrate and potassium nitrate, sodium sulfate, Sulfates such as sodium and potassium sulfate, and salts of alkali metals and alkaline earth metals. Some examples include:

[0085] <Step (II-2) of Producing a Laminate Having a Polarizing Film Impregnated with a Component in a Liquid> The method for producing the polarizing film (thin polarizing film) of the present invention comprises the steps of: A step of applying a liquid to the laminate having the polarizing film is performed while the moisture content of the polarizing film is Y% by weight or more. and producing a laminate having a polarizing film impregnated with a component in the liquid (II-2). In the step (II-2), a polarizing film impregnated with the above-mentioned liquid components is produced. However, the liquid is not applied to the surface of the polarizing film (coating method). )do.

[0086] In the step (II-2), the components contained in the liquid are easily impregnated into the polarizing film, and the polarizing film is From the viewpoint of making it easier for the light to penetrate in the opposite direction, the moisture content of the polarizing film (Y weight%) is set to 20 times. % by weight or more, and the moisture content of the polarizing film is preferably 22% by weight or more. It is more preferable that the moisture content of the polarizing film is 25% by weight or more. It is more preferable that the moisture content of the polarizing film is 65% by weight from the viewpoint of preventing wrinkles during transportation. It is preferable that the moisture content of the polarizing film is 60% by weight or less. It is more preferable to do so.

[0087] The time from the end of step (II-1) to the start of step (II-2) (in actual production) The transport time of the laminate having the polarizing film is determined based on the time required to retain the moisture contained in the water-containing polarizing film. From the viewpoint of productivity, the temperature is about 15°C to 35°C, preferably 2 It is preferable to heat the material at about 0°C to 30°C for 300 seconds or less, and more preferably for 180 seconds or less. More preferably, the time is 60 seconds or less, and even more preferably, the time is 10 seconds or less. Preferred.

[0088] In the step (II-2), the laminate having the water-containing polarizing film is It is preferable that the condition of formula (b) is satisfied. As a result, the thickness of the polarizing film after drying is increased. The boron content in the polarizing film in the laminate having the water-containing polarizing film is set accordingly. This allows the components in the liquid to permeate efficiently. Formula (b): A (weight%)<0.08×B(μm)+3.3 (In formula (b), A represents the boron content in the polarizing film in a laminate having a polarizing film containing water. is the content (wt%), and B is the thickness (μm) of the polarizing film after drying.

[0089] <Process for producing a dried polarizing film (II-3)> The method for producing the polarizing film (thin polarizing film) of the present invention comprises the steps of: A step of subjecting the laminate having the polarizing film to a drying treatment step to produce a dried polarizing film (I I-3).

[0090] The drying process may be carried out by any suitable method, for example, natural drying, air drying, heating, etc. The drying process may be performed by heating the entire zone. Alternatively, the heating may be performed by heating the transport roll (using a so-called heated roll). By drying using a heating roll, the heat curl of the laminate can be efficiently prevented. This suppresses the formation of the polarizing film, resulting in a polarizing film with excellent appearance, and also allows the laminate to be kept flat. This allows the hair to be dried while still being curled, preventing wrinkles as well as curling. During the drying process, the film is shrunk in the width direction to improve the optical properties of the resulting polarizing film. From the viewpoint of being able to reduce the shrinkage rate of the laminate in the width direction due to the drying process, the shrinkage rate of the laminate in the width direction is set to 1 to 10%. It is preferable that the content is about 10% or more, and more preferable that the content is about 2 to 8% or more.

[0091] Heating temperature of the transport roll (temperature of the heating roll), number of heating rolls, contact with the heating roll The drying conditions can be controlled by adjusting the heating roll temperature. The temperature is preferably about 0 to 120°C, and more preferably about 65 to 100°C. It is more preferable that the temperature is 70 to 80° C. In order to satisfactorily increase the crystallinity of the thermoplastic resin, From the viewpoint of suppressing curling, the number of conveying rolls is usually about 2 to 40. The number of contact times between the laminate and the heating roll is preferably about 4 to 30. The time is preferably about 1 to 300 seconds, and more preferably 1 to 20 seconds. It is more preferable that the time is 1 to 10 seconds.

[0092] The heating roll may be installed in a heating furnace or in a normal production line (at room temperature). It is preferable that the drying apparatus is installed in a heating oven equipped with a blowing means. By using hot air drying in combination, it is possible to suppress sudden temperature changes between the heating rolls. The shrinkage in the width direction can be easily controlled. The temperature for hot air drying is about 30 to 100°C. The hot air drying time is preferably about 1 to 300 seconds. stomach.

[0093] The method for producing a polarizing film of the present invention is based on the formula (3): Y (wt %) / thickness of the polarizing film after drying The condition that the thickness (μm) is greater than 1 is satisfied, preferably the formula (3) is greater than 1.5, and more preferably the formula (3) is greater than 1.5. is preferably formula (3)>2.0, and more preferably formula (3)>3.0.

[0094] In addition, the method for producing a polarizing film of the present invention is capable of increasing the degree of polarization when the film is in a polarizing film state. From this viewpoint, the above-mentioned Y (wt%)−the moisture content (wt%) of the polarizing film after drying> It is preferable that the condition (4) is 0 (wt%), and the condition (4) is > 2 (wt%). It is more preferable that the formula (4) is greater than 5 (wt %).

[0095] <Method of manufacturing polarizing film> The method for producing a polarizing film of the present invention is a method for producing a polarizing film by using at least one of the polarizing films obtained by the method for producing a polarizing film. The process also includes a step of laminating a transparent protective film to one side of the substrate via an adhesive layer.

[0096] The transparent protective film is not particularly limited, and may be any of various transparent films used in polarizing films. A protective film can be used. Examples of materials constituting the transparent protective film include For example, thermoplastic resins that are excellent in transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, etc. are used. Examples of the thermoplastic resin include cellulose such as triacetyl cellulose. Ester resins, polyesters such as polyethylene terephthalate and polyethylene naphthalate Polyether resin, polyethersulfone resin, polysulfone resin, polycarbonate resin Grease, polyamide resins such as nylon and aromatic polyamide, polyimide resins, polyethylene Polyolefin resins such as ethylene, polypropylene, and ethylene-propylene copolymers; p) Acrylic resins, cyclic polyolefins having a cyclo or norbornene structure Resin (norbornene resin), polyarylate resin, polystyrene resin, polyvinyl The transparent protective film may be made of an alcohol-based resin or a mixture thereof. , (meth)acrylic, urethane, acrylic urethane, epoxy, silicone, etc. A hardened layer formed from a thermosetting resin or an ultraviolet-curable resin can be used. Among these, cellulose ester resins, polycarbonate resins, (meth)acrylic Among these, preferred are polyolefin-based resins, cyclic polyolefin-based resins, and polyester-based resins.

[0097] The thickness of the transparent protective film can be appropriately determined, but is generally determined based on the workability such as strength and handling. From the viewpoints of the thickness and thinness, the thickness is preferably about 1 to 500 μm, and more preferably about 1 to 300 μm. It is more preferable that the thickness is at least about 5 to 100 μm, and further more preferable that the thickness is about 5 to 100 μm.

[0098] When the transparent protective film is attached to both sides of the polarizing film, the transparent protective film on both sides The films may be the same or different.

[0099] The transparent protective film has a front retardation of 40 nm or more and / or a thickness retardation A retardation plate having a retardation of 80 nm or more can be used. The thickness direction retardation is usually controlled in the range of 40 to 200 nm, and the thickness direction retardation is usually controlled in the range of 80 to 300 nm. When a retardation plate is used as the transparent protective film, the retardation plate is a transparent protective film. Since it also functions as a film, it can be made thinner.

[0100] The retardation plate may be, for example, a birefringent plate obtained by uniaxially or biaxially stretching a polymer material. A film supporting the orientation layer of the liquid crystal polymer. The thickness of the retardation plate is not particularly limited, but is preferably about 20 to 150 μm. In addition, the phase plate is attached to a transparent protective film that does not have a phase difference. may be used.

[0101] The transparent protective film may contain ultraviolet absorbing agents, antioxidants, lubricants, plasticizers, release agents, colorants, etc. Any suitable additives may be included, such as inhibitors, flame retardants, antistatic agents, pigments, colorants, etc. .

[0102] On the surface of the transparent protective film on which the polarizing film is not laminated, a hard coat layer and an anti-reflection layer are In addition, functional layers such as an anti-sticking layer, a diffusion layer, and an anti-glare layer can be provided. The above-mentioned hard coat layer, anti-reflection layer, anti-sticking layer, diffusion layer and anti-glare layer The functional layer can be provided on the protective film itself, or can be provided separately from the protective film. can also be provided as a separate entity.

[0103] The polarizing film and the transparent protective film, or the polarizing film and the functional layer, are usually bonded to each other by adhesive. The plates are attached via a layer of adhesive or a layer of glue.

[0104] The adhesive layer may be formed of any of various adhesives used in polarizing films. Examples of the adhesive include rubber-based adhesives, acrylic-based adhesives, silicone-based adhesives, and urethane-based adhesives. vinyl alkyl ether adhesives, polyvinyl alcohol adhesives, polyvinyl Examples of such adhesives include polyproporol-based adhesives, polyacrylamide-based adhesives, and cellulose-based adhesives. Among these, acrylic adhesives are preferable.

[0105] The method for forming the adhesive layer is, for example, to apply the adhesive to a separator or the like that has been subjected to a release treatment. A method of applying the adhesive layer to a polarizing film or the like, drying the adhesive layer, and then transferring the adhesive layer to a polarizing film or the like. The adhesive layer may be formed by applying the adhesive to a polarizing film or the like and drying the applied adhesive. The thickness is not particularly limited and is, for example, about 1 to 100 μm, and about 2 to 50 μm. It is preferable.

[0106] The adhesive for forming the adhesive layer may be any of various adhesives used in polarizing films. For example, an isocyanate-based adhesive, a polyvinyl alcohol-based adhesive, a gelatin Examples of adhesives include vinyl-based adhesives, vinyl latex-based adhesives, and water-based polyester adhesives. It is usually used as an adhesive consisting of an aqueous solution, and contains 0.5 to 60% by weight of solids. become.

[0107] In addition to the above, the adhesive may be an active agent such as an ultraviolet-curing adhesive or an electron beam-curing adhesive. Examples of the active energy ray curable adhesive include: For example, a (meth)acrylate adhesive can be mentioned. The curable component in the above formula (1) is, for example, a compound having a (meth)acryloyl group, a vinyl In addition, compounds having epoxy groups or olefin groups are used as cationic polymerization curing adhesives. Compounds having xetanyl groups can also be used. Compounds having epoxy groups can also be used. There are no particular limitations on the type of epoxy resin as long as it has at least two epoxy groups in the molecule. Various curable epoxy compounds known in the art can be used.

[0108] The adhesive is applied to the transparent protective film side (or the functional layer side) and the polarizing film side. After lamination, a drying process is performed, and the coating is then After the drying step, the adhesive layer is dried by exposing the adhesive layer to ultraviolet light or electricity, if necessary. The thickness of the adhesive layer is not particularly limited, and a water-based adhesive or the like may be used. When used, the thickness is preferably about 30 to 5000 nm, and more preferably 100 to 1000 nm. It is more preferable that the thickness is about 100 nm, and when an ultraviolet-curing adhesive, an electron beam-curing adhesive, or the like is used, In this case, the thickness is preferably about 0.1 to 100 μm, and more preferably about 0.5 to 10 μm. is more preferable.

[0109] The transparent protective film and the polarizing film, or the polarizing film and the functional layer, are subjected to a surface modification treatment. The laminate may be laminated via an intermediate layer such as a protective layer, an easy-adhesive layer, a blocking layer, or a refractive index adjusting layer. .

[0110] Examples of the surface modification treatment for forming the surface modification layer include corona treatment and plasma treatment. , primer treatment, saponification treatment, etc.

[0111] The adhesive for forming the adhesive layer may be, for example, a polyester skeleton, a polyether skeleton, skeleton, polycarbonate skeleton, polyurethane skeleton, silicone-based, polyamide skeleton, poly Examples of the material include forming materials containing various resins having an imide skeleton, a polyvinyl alcohol skeleton, or the like. The easy-adhesion layer is usually provided in advance on the protective film, and the easy-adhesion layer side of the protective film is and the polarizing film are laminated with the pressure-sensitive adhesive layer or the adhesive layer.

[0112] The blocking layer is formed by blocking impurities such as oligomers and ions eluted from a transparent protective film, etc. The block is a layer having a function of preventing the migration (penetration) of the block into the polarizing film. The layer is transparent and can prevent impurities from being eluted from a transparent protective film, etc. The material for forming the block layer may be, for example, a urethane prepolymer-based forming material, Examples of the material include cyanoacrylate-based forming materials and epoxy-based forming materials.

[0113] The refractive index adjusting layer is used to adjust the reflection between layers having different refractive indices, such as the transparent protective film and the polarizing film. The refractive index adjusting layer is a layer provided to suppress the decrease in transmittance caused by the above-mentioned. Examples of the refractive index adjusting material include silica-based, acrylic-based, acrylic-styrene-based, and melamine-based materials. Examples of the forming agent include various resins having a resin system and additives.

[0114] The polarizing film preferably has a polarization degree of 99.98% or more. .99% or higher is more preferable. EXAMPLES

[0115] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples. However, the present invention is not limited to the above.

[0116] <Example 1> <Production of polarizing film> <Production of polarizing film containing water (I-1)> Polyvinyl chloride with an average polymerization degree of 2,400, a saponification degree of 99.9 mol%, and a thickness of 45 μm. The polyvinyl alcohol film was prepared. Between rolls, the sheet is immersed in a swelling bath (water bath) at 20°C for 30 seconds to swell and rotate at a speed of 2.2°C in the conveying direction. The fabric is stretched to 100% by weight (swelling step), and then immersed in a dye bath at 30° C. (iodine concentration: 0.03% by weight, The original polyester fiber was dyed by immersing it in a 0.3% by weight aqueous solution of potassium chloride for 30 seconds. Polyvinyl alcohol film (a polyvinyl alcohol film that is not stretched in the machine direction) The dyed polyester film was stretched 3.3 times in the conveying direction based on the film thickness (dyeing process). The vinyl alcohol film was placed in a crosslinking bath (boric acid concentration 3.0 wt.%, potassium iodide concentration 1.0 wt.%) at 40°C. The original polyvinyl alcohol was then immersed in an aqueous solution containing 3.0% by weight of ethanol for 28 seconds. The film was stretched to 3.6 times in the conveying direction (crosslinking step). The polyvinyl alcohol film was placed in a 61°C stretching bath (boric acid concentration 4.0 wt.%, iodine The original polyvinyl alcohol was then immersed in an aqueous solution containing 5.0% potassium for 60 seconds. The film was stretched 6.0 times in the conveying direction (stretching process), and then washed at 20°C. Immerse in a cleaning bath (aqueous solution with a potassium iodide concentration of 2.0% by weight) for 5 seconds (cleaning process). Thus, a water-containing polarizing film was produced.

[0117] <Production of polarizing film impregnated with liquid components (I-2)> Using a wire bar (No. 3, manufactured by Daiichi Rikagaku Co., Ltd.), Liquid A (a 10% by weight aqueous solution of the compound represented by the following chemical formula (9)) is applied to the polarizing film. After leaving it at 25°C for 3 seconds, wipe off the liquid A remaining on the surface and check whether the components in the liquid have been impregnated. The moisture content of the water-containing polarizing film was measured by the following method. The rate was 33.0% by weight. [ka]

[0118] [Method for measuring moisture content (weight%) in polarizing film] Approximately 0.2 g of the polarizing film was weighed out and dried at 120°C for 2 hours. The weight after drying was measured and the polarizing film was The moisture content (W) in the light-transmitted film was calculated based on the following formula. Moisture content of polarizing film W (weight%) = {(M0-M1) / M0} x 100 M0: Measured weight of polarizing film (g) M1: Weight of polarizing film after drying for 2 hours at 120℃ (g)

[0119] [Method for measuring boron content (wt%) in polarizing film containing water] The above water-containing polarizing film (0.2-0.3 g) was dried at 120°C for 2 hours, and then the water A small amount of mannitol and BTB solution was added dropwise to the aqueous solution, and 0.1 mol / L The NaOH aqueous solution was neutralized by titration using a burette, and the boron content of the polarizing film was calculated based on the following formula: The calculation was made. Boron content of polarizing film containing water (% by weight) = C × V × Mw / M × 100 C: Concentration of NaOH solution (mol / L) V: Amount of NaOH solution dropped (L) Mw: Atomic weight of boron (g / mol) M: Weight of polarizing film after drying at 120℃ for 2 hours (g)

[0120] <Production of polarizing film after drying (I-3)> The polarizing film impregnated with the liquid components obtained above was dried at 60°C for 4 minutes. The polarizing film after drying was measured by the above-mentioned measurement method. The moisture content of the polarizing film was 11.3% by weight. (9) Content of the compound represented by (M H ) is 0.27% by weight, and the oxidation rate per unit area is The content of the compound represented by formula (9) (m H ) is 5.4μg / cm 2 Also, The thickness (T) of the light film was 18 μm.

[0121] [Method for measuring the content (wt%) of the compound represented by chemical formula (9) in the polarizing film] Approximately 20 mg of the polarizing film was collected and weighed, dissolved in 1 mL of water by heating, and then dissolved in 4.5 mL of methanol. The extract was diluted with 1 mL of hexane and filtered through a membrane filter. The filtrate was then analyzed by HPLC (Wa The chemical formula ( 9) The concentration of the compound shown in

[0122] [Content of the compound represented by chemical formula (9) per unit area in the polarizing film (μg / cm 2 ) Measurement method] The content of the compound represented by chemical formula (9) per unit area (m H ) is calculated based on the following formula: I put it out. m H =1.2×T×MH (μg / cm 2 ) T: Thickness of the polarizing film (μm) M H : Content (wt%) of the compound represented by chemical formula (9) in the polarizing film

[0123] <Production of polarizing film> As an adhesive, polyvinyl alcohol resin containing acetoacetyl groups (average degree of polymerization is 1,200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and methylol An aqueous solution containing melamine in a weight ratio of 3:1 was used. The polarizing film is a 40 μm-thick triacetyl cellulose film with a hard coat layer on both sides. Moisture permeability is 342g / (m 2 24h), manufactured by Konica Minolta, product name "KC4UYW After laminating the two sheets with a roll laminating machine, they are then heated and dried in an oven (at a temperature of 60°C, After the polarizing film was left to stand for 4 minutes, the polarizing film was We manufactured the product.

[0124] [Method of measuring the degree of polarization] The degree of polarization of the polarizing film was measured using a spectrophotometer (manufactured by JASCO, product name "V7100") The degree of polarization can be measured by measuring the parallel transmittance (H0 ) and cross transmittance (H90) were measured, and the formula: Polarization degree (%) = {(H0-H90) / (H0 +H90)}1 / 2×100. The parallel transmittance (H0) is the Transmission of parallel-type laminated polarizing film made by stacking two films so that their absorption axes are parallel to each other The crossed transmittance (H90) is the value obtained when two polarizing films are arranged with their absorption axes perpendicular to each other. The transmittance of these cross-type laminated polarizing films is shown in Fig. The transmittance is corrected for visibility using the 2-degree field of view (C light source) of JLS Z 8701-1982. This is the Y value.

[0125] [Heat durability rating (A)] The polarizing film obtained above was placed in a 5.0×4 Cut the film into pieces measuring 2.5 cm in length and attach it to the protective film on the image display cell side of the polarizing film. A glass plate (pseudo image display cell) was attached via a 50 μm thick acrylic adhesive layer. The laminate was then autoclaved at 0.5 MPa for 15 minutes to prepare a laminate. The specimen was placed in a hot air oven at 110°C and the time until coloration occurred was visually observed according to the following criteria: It was judged as follows. Good: No coloring for more than 500 hours. △: Coloration occurred after 300 hours or more and less than 500 hours. ×: Coloration occurred within 300 hours.

[0126] [Heat durability rating (B)] The polarizing film obtained above was placed in a 5.0×4 Cut the film into pieces measuring 2.5 cm in length and attach it to the protective film on the image display cell side of the polarizing film. A glass plate (pseudo image display cell) was attached via a 50 μm thick acrylic adhesive layer. The laminate was then autoclaved at 0.5 MPa for 15 minutes to prepare a laminate. The specimen was placed in a hot air oven at 105°C and the time until coloration occurred was visually observed according to the following criteria: It was judged as follows. Good: No coloring for more than 750 hours. △: Coloration occurred after 750 hours or more and less than 500 hours. ×: Coloration occurred within 500 hours.

[0127] <Example 2> <Production of polarizing membranes and polarizing films> The polarizing film after the washing step was left to stand at 25°C for 30 seconds to obtain a polarizing film containing water. A polarizing film and a polarizing membrane were produced in the same manner as in Example 1, except that A was applied. The results are shown in Table 1.

[0128] <Example 3> <Production of polarizing membranes and polarizing films> The polarizing film after the washing process was left to stand at 25°C for 1 minute to obtain a polarizing film containing water, and then liquid A was added. A polarizing film and a polarizing membrane were produced in the same manner as in Example 1, except that The above measurements were carried out, and the results are shown in Table 1.

[0129] <Comparative Example 1> <Production of polarizing membranes and polarizing films> The polarizing film after the washing process was left to stand at 25°C for 3 minutes to obtain a polarizing film containing water, and then liquid A was added. A polarizing film and a polarizing membrane were produced in the same manner as in Example 1, except that The above measurements were carried out, and the results are shown in Table 1.

[0130] <Comparative Example 2> <Production of polarizing membranes and polarizing films> After the cleaning process, the polarizing film was dried at 60°C for 1 minute, and then liquid A was applied to it. A polarizing membrane and a polarizing film were produced in the same manner as in Example 1, and the above measurements were carried out. The results are shown in Table 1.

[0131] <Comparative Example 3> <Production of polarizing membranes and polarizing films> In the process (I-3) for producing the dried polarizing film, heat drying at 60°C for 4 minutes is not performed. A polarizing film and a polarizing membrane were prepared in the same manner as in Example 1, except that the polarizing membrane and the polarizing film were not prepared. The following measurements were carried out, and the results are shown in Table 1.

[0132] <Example 4> <Production of polarizing membranes and polarizing films> The final polarizing film is made of a 30 μm thick polyvinyl alcohol film. The same procedure was repeated as in Example 1, except that the iodine concentration in the dye bath was adjusted so that the single transmittance of A polarizing membrane and a polarizing film were produced in the same manner as in the above, and the above measurements were carried out. 1. The thickness (T) of the polarizing film was 12 μm.

[0133] <Comparative Example 4> <Production of polarizing membranes and polarizing films> After the cleaning process, the polarizing film was dried at 60°C for 1 minute, and then liquid A was applied to it. A polarizing membrane and a polarizing film were produced in the same manner as in Example 4, and the above measurements were carried out. The results are shown in Table 1.

[0134] <Example 5> <Production of polarizing film> <Laminate manufacturing (preparation) (II-0)> The thermoplastic resin substrate is a long, amorphous material with a water absorption rate of 0.75% and a Tg of approximately 75°C. The isophthalic copolymer polyethylene terephthalate film (thickness: 100 μm) was used. One side of the resin substrate was subjected to corona treatment. Polyvinyl chloride (99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product number: 100 parts by weight of PVA resin mixed with GOHSEFYMER Z410 in a ratio of 9:1 13 parts by weight of potassium fluoride was added to prepare a PVA aqueous solution (coating solution). The PVA aqueous solution was applied to the treated surface and dried at 60°C to form a 13μm thick film. A PVA-based resin layer was formed, and a laminate was manufactured (prepared).

[0135] <Step (II-1) of Producing a Laminate Having a Water-Containing Polarizing Film> The obtained laminate was then rolled in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130°C. The laminate was then stretched uniaxially at its free end to 2.4 times its original length (auxiliary air stretching process). Insolubilizing bath at 40°C (100 parts by weight of water and 4 parts by weight of boric acid) The fabric was then immersed in a dye bath (100 ml of water) at a temperature of 30° C. for 30 seconds (insolubilization treatment step). 00 parts by weight of iodine and potassium iodide in a weight ratio of 1:7. The concentration of the solution was adjusted so that the final polarizing film had a single transmittance (Ts) of 42%. The fabric was then immersed in a crosslinking bath (water) at a liquid temperature of 40° C. for 60 seconds while adjusting the temperature (dyeing process). For 100 parts by weight, 3 parts by weight of potassium iodide and 5 parts by weight of boric acid are mixed. The laminate was then immersed in the aqueous solution of boric acid (aqueous solution of boric acid) for 30 seconds (crosslinking treatment step). The rod was immersed in a 70°C boric acid solution (boric acid concentration 4.0% by weight) and rotated at different speeds. The film was uniaxially stretched between the tubes in the longitudinal direction (longitudinal direction) to a total stretch ratio of 5.5 times (underwater stretching). After that, the laminate was washed in a washing bath at 20°C (100 parts by weight of water, 100 parts by weight of iodine The film was immersed in an aqueous solution containing 4 parts by weight of potassium hydroxide. A laminate was produced (cleaning treatment step).

[0136] <Production of a laminate having a polarizing film impregnated with a liquid component (II-2)> Using a wire bar (No. 3, manufactured by Daiichi Rikagaku Co., Ltd.), Liquid A (a compound represented by chemical formula (9) 10 times) was applied to the polarizing film surface of the laminate having the polarizing film. % aqueous solution) was applied to the surface, and the surface was left to stand at 25°C for 3 seconds. Liquid A remaining on the surface was then wiped off. A laminate having a polarizing film impregnated with the components in the liquid was produced. The moisture content of the water-containing polarizing film was determined to be 35.5% by weight.

[0137] <Production of polarizing film after drying (II-3)> The mixture was dried in an oven maintained at 95°C for 10 minutes (drying process). A polarizing film having a thickness of 5 μm was formed on a resin substrate. The polarizing film after drying was measured by the above-mentioned measurement method. The moisture content of the film was 9.9% by weight. The content of the compound represented by chemical formula (9) in the polarizing film (M H ) is 0.41% by weight, and the content of the compound represented by the chemical formula (9) per unit area is Quantity (m H ) is 2.5μg / cm 2 It was.

[0138] <Production of polarizing film> As an adhesive, polyvinyl alcohol resin containing acetoacetyl groups (average degree of polymerization is 1,200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and methylol An aqueous solution containing melamine in a weight ratio of 3:1 was used. A 40 μm-thick triacetylacetone film having a hard coat layer on the opposite side to the resin substrate of the polarizing film. Lubricant film (moisture permeability 342g / (m 2 24h), manufactured by Konica Minolta, product name " After laminating the two sheets using a roll laminating machine, they were then heated and dried in an oven ( After the polarizing film was heated at 60°C for 4 minutes, a transparent protective film was attached to one side of the polarizing film. The resin substrate was then peeled off, and the above-mentioned adhesive was used on the peeled surface to produce a polarizing film. The triacetyl cellulose film was then laminated using a roll laminating machine, and then Heat-dry in an oven (at 60°C for 4 minutes) to form a transparent protective film on both sides of the polarizing film. A polarizing film was produced by laminating the film.

[0139] [Heat durability rating (C)] The polarizing film obtained above was placed in a 5.0×4 Cut the film into pieces measuring 2.5 cm in length and attach it to the protective film on the image display cell side of the polarizing film. A glass plate (pseudo image display cell) was attached via a 50 μm thick acrylic adhesive layer. The laminate was then autoclaved at 0.5 MPa for 15 minutes to prepare a laminate. The specimen was placed in a hot air oven at 95°C and the time it took for the specimen to become discolored was visually observed according to the following criteria: The decision was made. Good: No coloring for more than 750 hours. △: Coloration occurred after 750 hours or more and less than 500 hours. ×: Coloration occurred within 500 hours.

[0140] <Comparative Example 5> <Production of polarizing membranes and polarizing films> After the cleaning process, the polarizing film was dried at 95°C for 10 minutes and then coated with Liquid A. In the same manner as in Example 5, a polarizing film and a polarizing membrane were produced, and the above measurements were carried out. The results are shown in Table 2.

[0141] <Example 6> <Production of polarizing membranes and polarizing films> In the manufacture of polarizing films, the potassium iodide concentration in the cleaning bath was set to 4.0% by weight. Instead of liquid A, liquid B (10% by weight of zinc sulfate heptahydrate and Olefin EXP.4 200 (manufactured by Nissin Chemical Industry Co., Ltd.) (aqueous solution containing 0.2% by weight) was used. A polarizing membrane and a polarizing film were produced in the same manner as in Example 1, and the above and following measurements were carried out. The results are shown in Table 3.

[0142] [Measurement of zinc content (wt%) in polarizing film] Approximately 25 mg of polarizing film was weighed into a Teflon (registered trademark) container, acid was added, and the container was sealed. After complete decomposition, ultrapure water was added to make the volume 50 mL. The volume was adjusted to a constant value and the sample was analyzed by ICP-MS (Agilent Technologies, The zinc concentration was measured using a CEM MARS5 decomposition device. .

[0143] [Heat durability rating (D)] The polarizing film obtained above was placed in a 5.0×4 Cut the film into pieces measuring 2.5 cm in length and attach it to the protective film on the image display cell side of the polarizing film. A glass plate (pseudo image display cell) was attached via a 50 μm thick acrylic adhesive layer. The laminate was then autoclaved at 0.5 MPa for 15 minutes to prepare a laminate. The specimen was placed in a hot air oven at 105°C for 500 hours, and the specimen was then placed in a cross-Nicol The cross transmittance (%) at a wavelength of 700 nm was measured using the spectrophotometer (V7100) mentioned above. Each was measured and judged according to the following criteria. ○: No red discoloration due to heat (cross transmission at a wavelength of 700 nm before and after a heating test at 105°C for 500 hours) The rate difference is less than 1%. ×: Red discoloration due to heat (cross transmission at a wavelength of 700 nm before and after a heating test at 105°C for 500 hours) (The difference in rates is 1% or more.)

[0144] <Comparative Example 6> <Production of polarizing membranes and polarizing films> After the cleaning process, the polarizing film was dried at 60°C for 1 minute, and then liquid B was applied to it. A polarizing membrane and a polarizing film were produced in the same manner as in Example 6, and the above measurements were carried out. The results are shown in Table 3.

[0145] [Table 1]

[0146] [Table 2]

[0147] [Table 3]

[0148] The above heat durability test is affected by the thickness of the polarizing film, so The polarizing film of the embodiment has a higher optical transparency than the polarizing film of the comparative example. It is clear that the composition contains sufficient components and therefore has excellent heat durability.

Claims

1. A method for producing a polarizing film, comprising the steps of: a step (I-1) of producing a water-containing polarizing film by subjecting the polyvinyl alcohol-based film to at least a dyeing step, a crosslinking step, and a stretching step while transporting the polyvinyl alcohol-based film in a longitudinal direction; a step (I-2) of applying a liquid (excluding a treatment liquid having a pH in the range of 3 to 8 and having a buffering effect in said pH range) to the obtained water-containing polarizing film while the moisture content of the polarizing film is at least X% by weight, thereby producing a polarizing film impregnated with a component in the liquid; a step (I-3) of subjecting the polarizing film impregnated with the components in the obtained liquid to a drying step to produce a polarizing film after drying having a moisture content of 20% by weight or less; applying an adhesive to the liquid-coated surface of the resulting dried polarizing film, and laminating a transparent protective film thereon via the adhesive layer; Formula (1): X (wt %) / thickness (μm) of the polarizing film after drying>1 (In formula (1), X is 10 or more and 70 or less.) The method for producing a polarizing film is characterized by satisfying the following conditions:

2. Formula (2): X (wt %)-moisture content (wt %) of the polarizing film after drying>0 (wt %) (In formula (2), X is 10 or more and 70 or less.) 2. The method for producing a polarizing film according to claim 1, wherein the following condition is satisfied:

3. A method for producing a polarizing film, comprising the steps of: A step (II-0) of preparing a laminate by forming a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin on one side of a long thermoplastic resin substrate; a step (II-1) of carrying out at least an auxiliary air-stretching step, a dyeing step, and an underwater stretching step on the obtained laminate while conveying the laminate in the longitudinal direction to produce a laminate having a water-containing polarizing film; a step (II-2) of applying a liquid (excluding a treatment liquid having a pH in the range of 3 to 8 and having a buffering effect in said pH range) to the obtained laminate having the water-containing polarizing film while the moisture content of the polarizing film is Y% by weight or more, thereby producing a laminate having a polarizing film impregnated with a component in the liquid; a step (II-3) of subjecting the laminate having the polarizing film impregnated with the components in the liquid to a drying treatment step to produce a polarizing film after drying having a moisture content of 20% by weight or less; applying an adhesive to the liquid-coated surface of the resulting dried polarizing film, and laminating a transparent protective film thereon via the adhesive layer; Formula (3): Y (% by weight) / thickness (μm) of the polarizing film after drying>1 (In formula (3), Y is 10 or more and 70 or less.) The method for producing a polarizing film is characterized by satisfying the following conditions:

4. Formula (4): Y (wt %)-moisture content (wt %) of the polarizing film after drying>0 (wt %) (In formula (4), Y is 10 or more and 70 or less.) 4. The method for producing a polarizing film according to claim 3, wherein the above condition is satisfied.

5. 5. The method for producing a polarizing film according to claim 1, wherein the liquid is a solution, and a component in the liquid is a solute.

6. 6. The method for producing a polarizing film according to claim 1, wherein the component in the liquid is a water-soluble compound.

7. 7. The method for producing a polarizing film according to claim 1, wherein the component in the liquid is at least one selected from the group consisting of a radical scavenger, a crosslinking agent, a plasticizer, and a dye.

8. The method for producing a polarizing film according to any one of claims 1 to 7, wherein the component in the liquid is a radical scavenger.

Citation Information

Patent Citations

  • Method of alkali saponification of cellulose ester film, surface saponified cellulose ester film and optical film using the same

    JP2004203965A

  • Polarizing plate, optical member provided with the same and liquid crystal display device

    JP2008257025A

  • Method for manufacturing polarizing plate

    JP2013178356A

  • Polarizing plate, liquid crystal display device comprising the same, and method for producing polarizing plate

    JP2015180910A

  • Polarizing plate, liquid crystal display device including the same, and manufacturing method of polarizing plate

    JP2016045434A